Long-term effectiveness of the nine-valent human papillomavirus vaccine in Scandinavian women: interim analysis after 8 years of follow-up. Issue 4 (3rd April 2021) - Kjaer, Susanne K.; Nygård, Mari; Sundström, Karin; Munk, Christian; Berger, Sophie; Dzabic, Mensur; Fridrich, Katrin Elisabeth; Waldstrøm, Marianne; Sørbye, Sveinung Wergeland; Bautista, Oliver; Group, Thomas; Luxembourg, Alain
ABSTRACT: A long-term follow-up (LTFU) of the nine-valent human papillomavirus (9vHPV) vaccine efficacy study in young women aged 16–26 years was initiated to evaluate if vaccine effectiveness for up to 14 years post-vaccination will remain above 90%. Vaccine effectiveness is measured as percent reduction in the incidence of HPV16/18/31/33/45/52/58-related high-grade cervical dysplasia in the LTFU cohort relative to expected incidence in a similar unvaccinated cohort. We report an interim analysis 8 years post-vaccination. Overall, 2029 participants from Denmark, Norway, and Sweden who received the 9vHPV vaccine during the clinical efficacy study continued into the LTFU study. National health registries were used to identify screening attendance and cervical pre-cancer/cancer diagnoses. Tissue samples were retrieved for HPV testing by PCR and pathology diagnosis adjudication. A control chart method was used to detect signals indicative of vaccine effectiveness waning below 90%. No new cases of HPV16/18/31/33/45/52/58-related high-grade cervical dysplasia were observed during the LTFU study period over 4084.2 person-years' follow-up (per-protocol effectiveness population; n = 1448). Thus, there were no signals indicative of vaccine effectiveness waning below 90%. These observations show that the 9vHPV vaccine provides continued statistically significant protection through at least 6 years, with indications of continued effectiveness through 8 years. Trial registration: Clinicaltrials.gov: NCT00543543, NCT02653118.